ANTIBACTERIAL AND IMMUNOTROPIC PROPERTIES OF ISOLIQUIRITIGENIN IN GENERALIZED STAPHYLOCOCCAL INFECTION IN MICE - E. A. Solyonova; S. I. Pavlova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2020)
The article is devoted to the study of the effects of isoliquiritigenin in generalized bacterial infections.The aim is to study antibacterial and immunotropic mechanisms and effects of isoliquiritigenin in generalized staphylococcal infections in a mouse model.Materials and methods. To assess the survival rate of Balb/C mice, a generalized infection model caused by Staphylococcus aureus J49 ATCC 25923 with Kaplan-Meier curves was used. The degree of bacteremia during the development of infection was determined by the method of sector crops. The minimum inhibitory concentration of isoliquiritigenin against Staphylococcus aureus J49 ATCC 25923 was determined by serial dilutions methods. To study an antibiofilm activity, the MTT test and atomic force microscopy were used. Immunotropic effects were studied by assessing peptone-induced migration of phagocytes into the abdominal cavity, proliferation of mitogen-activated lymphocytes in the MTT test and their cytokine secretion using the MILLIPLEX MAP kit on a Magpix multiplex analyzer.Results. It has been established that a preliminary intraperitoneal administration of isoliquiritigenin (30 mg/kg) increases the survival rate of Balb/C mice in case of generalized staphylococcal infections. Isoliquiritigenin has antibacterial (MOC = 64 μg/ml) and antibiofilm (4-32 μg/ml) activities against S. aureus J49 ATCC 25923, does not inhibit the migration of phagocytes in the abdominal cavity, dose-dependently inhibits the proliferation and secretion of cytokines by mitogenactivated T-lymphocytes and modulates the production of cytokines (IL-2, IL-12p70, IFNg, TNFα, IL-6, IL-22, IL-23, IL-17A, IL-17F, IL-17E/IL-25, GM-CSF, MIP - 3a/CCL20, IL-10) by the cells of inguinal lymph nodes and splenocytes in the early stages of generalized staphylococcal infections.Conclusion. A preliminary administration of isoliquiritigenin increases the survival rate of mice with generalized staphylococcal infections, which may be associated with both antimicrobial (antistaphylococcal, antibiofilm) and immunotropic mechanisms. The obtained data on the pharmacodynamics of isoliquiritigenin deserve attention from the point of view of the prospects of the new drugs creation that reduce mortality in staphylococcal sepsis.